2019
DOI: 10.1111/iej.13165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of larger apical size on the quality of preparation in curved canals using reciprocating instruments with different heat thermal treatments

Abstract: Aim To evaluate the influence of larger apical canal enlargement in curved canals using reciprocating systems subjected to various heat treatments. Methodology Ninety mandibular premolars with root curvatures ranging from 20° to 30° were selected and scanned by microcomputed tomography (micro‐CT) before and after root canal preparation with reciprocating systems (n = 30): Reciproc Blue (RB size 25, .08 taper and size 40, .06 taper; VDW, Munich, Germany), WaveOne Gold (WOG size 25, .07 taper and size 35, .06 ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 29 publications
1
25
2
3
Order By: Relevance
“…8,9 ProDesign Logic and ProDesign R are single-file mechanical systems (Easy Equipamentos Odontológicos, Belo Horizonte, Brazil) manufactured in control memory (CM) wire alloy. 9,10 The former performs continuous rotation or reciprocating motion and is available in four different tip sizes/tapers: 25.06, 30.05, 35.05, and 40.05 to be selected according to the initial diameter of the canals. The latter exclusively reciprocates with a variable helical angle and a counterclockwise cut.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 ProDesign Logic and ProDesign R are single-file mechanical systems (Easy Equipamentos Odontológicos, Belo Horizonte, Brazil) manufactured in control memory (CM) wire alloy. 9,10 The former performs continuous rotation or reciprocating motion and is available in four different tip sizes/tapers: 25.06, 30.05, 35.05, and 40.05 to be selected according to the initial diameter of the canals. The latter exclusively reciprocates with a variable helical angle and a counterclockwise cut.…”
Section: Introductionmentioning
confidence: 99%
“…It is available in two instruments with different tip sizes/tapers: 25.06 and 35.05. 10 Both systems presented S-shaped cross-sections with two cutting edges and inactive points. 9,10 Information regarding disinfection and apical debris extrusion is available for most systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, chronic apical lesion healing in dogs' teeth was reported to be more favorable in teeth with apical enlargement [ 5 ]. Large apical preparations were associated with better cleanliness of the root canal and less untouched places within the root canal system in extracted teeth with curved root canals [ 44 ]. These results were compatible with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the need for mechanized systems to be able to properly shape the canal, it is also important that the instruments have good mechanical properties such as good resistance to cyclic fatigue, especially in curved canals (DUQUE et al, 2019). Cyclic fatigue is characterized by successive tensile and compression loads that the metal undergoes at the maximum point of flexion until it exceeds the limit that the instrument supports, thus causing fracture (ALCALDE et al, 2018a;SILVA et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%